Light Chain Restriction in Proximal Tubules—Implications for Light Chain Proximal Tubulopathy - Büttner-Herold, Maike; Krieglstein, Nathalie; Chuva, Teresa; Minuth, Kaija; Pfister, Frederick; Daniel, Christoph; Klewer, Monika; Büttner, Anke; Ferrazzi, Fulvia; Bertz, Simone; Amann, Kerstin (Frontiers in Medicine, 2022)
Monoclonal gammopathy (MG) causes various nephropathies, which may suffice for cytoreductive therapy even in the absence of diagnostic criteria for multiple myeloma or B-cell Non-Hodgkin lymphoma. Objective: Aim of this study was to better understand the significance of light chain (LC) restriction or crystals in proximal tubules (LC-R/C) in the spectrum of light chain-induced nephropathies. A consecutive cohort of 320 renal specimens with a history of B-cell dyscrasia was characterized. Special attention was paid to immunohistochemical LC-restriction in proximal tubules, tubular crystals or constipation and ultrastructural findings. Complementary cell culture experiments were performed to assess the role of LC concentrations in generating LC-restriction. LC-R/C in proximal tubules was found in a quarter of analyzed cases (81/316) and was associated with another LC-induced disease in 70.4% (57/81), especially LC-cast-nephropathy (Cast-NP) and interstitial myeloma infiltration. LC-restriction without significant signs of acute tubular injury was observed in 11.1% (9/81). LC-R/C was not associated with inferior renal function compared to the remainder of cases, when cases with accompanying Cast-NP were excluded. Besides crystals, cloudy lysosomes were significantly associated with LC-R/C on an ultrastructural level. In summary, LC-R/C is frequent and strongly associated with Cast-NP, possibly indicating that a high load of clonal LC is responsible for this phenomenon, supported by the observation, that LC-restriction can artifically be generated in cell culture. This and the lack of significant tubular injury in a subgroup imply that in part LC-R/C is a tubular trafficking-phenomenon rather than an independent disease process.